Estratégias de participação na política de assistência social na perspectiva de Paulo Freire - Lemes, Marilene Alves (Universidade do Vale do Rio dos Sinos, 2017)
In this thesis the strategies of participation in social assistance policy with perspectives in Paulo Freire are analyzed, realizing to what extent they contribute or not to the understanding of participation as a principle. Methodologically, the research was characterized as a qualitative study, inspired by action research and participatory research. Data collection was done through observation, document analysis, reflection group - working group and interviews. During the interviews and analyzes, the research was supported by two collaborating researchers or "critical friends". The main theoretical foundation was Paulo Freire and the empirical field was the Social Development Secretariat of Novo Hamburgo City Hall, where 41 employees from the management segment collaborated directly in the role of subjects, where the researcher is also included. The research was conducted in order to raise the elements that explain the understanding of participation as a principle, from the strategies of participation, in social assistance policy, from a Freirian perspective. The analyzes allowed to conclude that: 1) the research itself was potentially formative with a significant contribution of the academy; 2) to investigate from the point of view of action research and participatory research required an effort to overcome an "egocentric" view due to strong affective identification with the empirical field of which the researcher was also a part; 3) Paulo Freire's theory, even though it is not directly mentioned in the documents analyzed, is identified in the understanding of authors of the Social Service area, of actors expressing their thoughts in the conferences, the CF and LOAS and in the discourse of the collaborating subjects. It is also manifested in the aims of social assistance policy and continues on the horizon as inspiration, as a utopian dimension to practices; 4) participation strategies contribute to the understanding of participation as a principle. However, resistance was also identified in breaking with coercive forms and attempts to co-opt the social control. In view of the relevance and quality of the contribution of the collaborating researchers, it is recommended to deepen this alternative to evaluate the feasibility of its incorporation in the qualitative research with approaches in action research and participatory research. In order for the principle of intersectoriality, which challenges for greater proactivity of social assistance, to become effective, it is suggested that it begin with a discussion of territoriality in dialogue with the other secretariats. Finally, autonomy and respect as indisputable elements of human experiences, commitment to the difficult task of humanizing the human, availability for the art of dialogue and learning, freedom as the ultimate principle of democratic practices and multifaceted understandings of participation, were themes and concepts raised in the dialogue with the empirical field, giving indications for a pedagogy of participation, also signaling new possibilities for research.
Keywords: Participação; Assistência social; Paulo Freire; Participation; Social assistance; ACCNPQ::Ciências Humanas::Educação